Growth Performance Studies in Thiram Toxicosis in Broiler Chicken - Subapriya, S.; Vairamuthu, S.; Manohar, B. Murali; Balachandran, C. (International Journal of Poultry Science, 2007)
Thiram a fungicide used for treating corn and storing food grains were incorporated at 15, 30 and 60 ppm into the toxin free diet of broiler chicken for four weeks from the day of hatch. Body weights (g) were recorded at weekly intervals. Average weekly feed consumption (g) and conversion were arrived at. The results showed that feeding thiram caused dose and time related severe depression in the body weight gain. Significant reduction in weight gain was observed from the first week in 60 ppm level and from second week in 30 ppm level. By fourth week all the thiram fed birds showed significant reduction in the weight gain.